A Retrospective Evaluation of the Benefit of Referring Pediatric Cancer Patients to an External Proton Therapy Center. Issue 2 (23rd September 2015) - Munck af Rosenschold, Per; Engelholm, Svend A.; Brodin, Patrik N.; Jørgensen, Morten; Grosshans, David R.; Zhu, Ronald X.; Palmer, Matthew; Crawford, Cody N.; Mahajan, Anita
Abstract : Background: Pediatric cancer patients requiring radiation therapy (RT) have been routinely assessed and referred to proton therapy (PT) at an external institution. The benefit of the delivered PT compared to the state‐of‐the‐art intensity modulated x‐ray RT (XT) at the home institution was evaluated. Procedure: Twenty‐four consecutive children referred for PT during 2010–2013 for craniospinal (CSI, n = 10), localized intracranial (IC, n = 7), head/neck (HN, n = 4) or parameningeal (PM, n = 3) lesions were included. The median age was 8 years (2–16 years). XT plans were generated for each patient, blinded to the PT delivered. Dosimetry, estimated growth hormone deficiency (GHD), and neurocognitive dysfunction (NCD) risks were compared for PT and XT (Wilcoxon). Results: PT started (median) 5 weeks (± 1.3 weeks, 95% CI) after referral. For CSI patients, PT was clearly superior to XT plans with median dose reductions for the heart, lungs and thyroid of 17, 2.5 and 18 Gy, respectively ( P  = 0.005). The median estimated NCD and GHD risks were 1–3 (max 16) and 2 (max 61) percentage points, respectively, lower for PT compared to XT. The median of the mean doses to the brain, cochleae and pituitary gland was lower with PT than XT for the IC, H/N and PM patients ( P  < 0.039). For a single IC patient, the dose to hippocampi and optic chiasm was higher for PT compared to XT. Conclusions: PT clearly benefitted the patients studied, except for IC disease where differences between PT and XT were modest, and comparative PT and XT treatment planning is warranted prior to referral. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.